Environmental Sustainability and Productivity of Australian Cattle Farming: A PRISMA-Guided Systematic Review - Mulyoto Pangestu; Supranoto Supranoto; Soegeng Herijanto (Faculty of Animal Husbandry, Wijayakusuma Purwokerto University, 2025)
This prisma guided systematic review synthesizes quantitative evidence on the environmental sustainability and productivity of Australian cattle farming systems. The review aims to identify management practices that enhance production performance while reducing environmental impacts. A comprehensive multi-database search identified 45 eligible peer-reviewed studies reporting quantitative outcomes such as average daily gain, feed efficiency, carcass traits, methane emissions, land footprint, and water use efficiency. Data harmonization and standardized effect size calculations were applied, and study quality was evaluated using validated risk-of-bias tools. Meta-analysis showed that rotational grazing and targeted dietary supplementation significantly improved productivity, with an average 8.5% increase in growth performance and a 12.3% reduction in methane intensity. Integrated interventions combining pasture improvement and nutritional strategies demonstrated synergistic effects, achieving up to a 10% improvement in productivity alongside an 18% decrease in greenhouse gas emissions per unit of beef. Heterogeneity analyses revealed that system type, regional ecological conditions, and herd characteristics strongly influenced intervention outcomes. Sensitivity analyses confirmed robustness, with minimal evidence of publication bias. Overall, the findings support the adoption of sustainable intensification practices including rotational grazing and feed efficiency enhancements to align productivity goals with environmental stewardship. Longterm, region-specific research remains essential to guide policy and industry strategies for sustainable beef production in Australia.